Determining the effect levels of augmented decent work criteria in sustainable economic development with the fuzzy dematel method - Baş, Halim; Ersin, İrfan; Kalkavan, Hakan (My University, 2025)
Creating decent work is among the priority issues for sustainable employment and development. This study aimed to determine the effect levels of the International Labour Organization (ILO) decent work criteria by augmenting nine indicators in the ILO manual to 12 criteria through a comprehensive literature review. Fuzzy DEMATEL, a multi-criteria decision-making method, has been preferred in this context. According to the analysis results of the study, the most heavily ranked criteria are ‘healthy workplace environment’, ‘decent working hours’ and ‘safe working conditions’ respectively, which contribute to the decent work concept. Further, ‘balance between work–family–personal life’ has been found the most affected criterion, while ‘education and training system’ has been the most affecting. Based on the findings, remedial and developing strategies are suggested on issues such as corporate culture, working hours regulation, safe working environment, subordinate–superior relations, social activities and regulations that take family life into account.
Keywords: Decent Work; Economic Sociology; Fuzzy DEMATEL; Sustainable Development; Welfare